ANALISIS EFEKTIVITAS MEDIA KOMUNIKASI VIRTUAL TERHADAP PEMAHAMAN MATERI PADA PEMBELAJARAN ONLINE - Sumarni, Sumarni (Hijri, 2024)
This study aims to analyze the effectiveness of virtual communication media on material comprehension in online learning at universities. The shift from face-to-face learning to online learning due to the Covid pandemic requires the use of virtual platforms such as Zoom, Google Meet, and Microsoft Teams as the main means of communication between lecturers and students. The research method used is quantitative descriptive with the distribution of questionnaires to students from various university faculties. The results show that virtual communication media play a significant role in improving material comprehension, especially when there is active interaction between teachers and students. A total of 72% of respondents stated that learning through virtual media was effective, while 18% said it was quite effective, and 10% said it was ineffective. The main factors affecting effectiveness were the quality of interaction, internet connection stability, and the ability of lecturers to utilize virtual media features. Thus, online learning can be an effective alternative if supported by technological readiness, interactive communication strategies, and adequate digital competence from all parties